Mode of Delivery and Neonatal Outcomes in Preterm Pregnancy - Gagah B. A. Nugraha; Nutria W. P. Anggraini (Indonesian Society of Obstetrics and Gynecology, 2023)
Objectives: To explain that mode of delivery has a correlation with neonatal outcomes in preterm pregnancies. Methods: This study is a retrospective cohort conducted at Dr. Moewardi Surakarta Hospital, with total sampling of 484 cases divided into early preterm and late preterm from 2019 to 2021. Bivariate analysis was carried out to determine the correlation between Mode of Delivery (MOD) and neonatal outcomes. Results: In the early preterm group, mode of delivery had a significant correlation (p<0.05) with birth weight, APGAR score, and neonatal mortality, however a significant correlation (p<0.05) in the late preterm group was only found in the APGAR score and neonatal mortality outcomes. Cesarean delivery, in both early and late preterm births had a lower rate of asphyxia and neonatal death (p<0.05). Conclusion: There is a significant correlation between mode of delivery and neonatal outcomes in preterm birth. Caesarean delivery by indication can significantly reduce the risk of asphyxia, and neonatal mortality due to premature birth. Keywords: mode of delivery, neonatal outcome, preterm. Abstrak Tujuan: Menjelaskan bahwa metode persalinan sangat berkorelasi dengan luaran neonatus pada kehamilan prematur, oleh karena itu penelitian ini dapat menjadi bahan pertimbangan untuk memilih metode persalinan. Metode: Penelitian ini merupakan penelitian kohort retrospektif yang dilakukan di RSUD Dr. Moewardi Surakarta, dengan total sampling sebanyak 484 kasus yang terbagi menjadi early preterm dan late preterm dari tahun 2019 hingga 2021. Analisis bivariat dilakukan dengan menggunakan analisis Chi-square dan Kruskal-Wallis untuk melihat korelasi antara metode persalinan (MOD) dan luaran neonatus Hasil: Pada kelompok early preterm, metode persalinan memiliki hubungan yang signifikan (p<0,05) dengan luaran neonatus baik berat lahir, skor APGAR, dan kematian neonatus. Pada kelompok late preterm, hubungan yang signifikan (p<0,05) hanya didapatkan pada luaran skor APGAR dan kematian neonatus. Persalinan Caesar baik early maupun late preterm memiliki angka yang lebih rendah terhadap asfiksia dan kematian neonatus (p<0,05). Kata kunci: metode persalinan, luaran neonatus, preterm.